BULLYING BEHAVIOR IN SCHOOLS IN THE PERSPECTIVE OF ISLAMIC PSYCHOLOGY - Titi Anjasari; Azam Syukur Rahmatullah (Psikoislamedia : Jurnal Psikologi, 2023)
Bullying behavior in schools has been going on for a long time and is still growing today. The purpose of writing this article is to discuss bullying behavior in schools in the perspective of Islamic Psychology. The method used in this writing is the study of libraries by taking literature from the Quran and Hadith, journals through google scholar and scopus, news and related books. The results of this study show that bullying behavior in schools in the perspective of Islamic Psychology is abusive behavior that a person does to others in verbal or physical form according to an Islamic point of view. This behavior can result in mental disorders even to suicide. Efforts to overcome bullying are to instill awareness as early as possible about the bullying virus and give love to children. For victims of bullying who experience mental disorders are given guidance and forgiveness techniques, al-Tasywiq and al-Tadzkir, Tsawab and Iqab, tazkiyah and ta'lim al-hikmah.Â